Sovereignty, knowledge, law [ - Minkkinen, Panu (Routledge, 2009)
Investigates the notion of sovereignty from three different, but related perspectives - as a legal question in relation to the sovereign state, as a political question in relation to sovereign power, and as a metaphysical question in relation to sovereign self-knowledge